THE IMPACT OF WORK LIFE BALANCE AND WORKLOAD ON JOB SATISFACTION THROUGH EMPLOYEE WORK MOTIVATION IN PRIVATE UNIVERSITY IN TEBING TINGGI - Rotua Sri Linda Sitompul; Sri Rahayu; Aisyah Siregar; Christin Sianipar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of Work-Life Balance and Workload on Job Satisfaction through Work Motivation among administrative staff at private higher education institutions in Tebing Tinggi City. The research employs a quantitative approach with an explanatory research design, which seeks to explain causal relationships between variables through hypothesis testing. The population in this study consists of 38 administrative staff members, with a total sampling technique used: 24 from STIE Bina Karya and 14 from STAI Tebing Tinggi Deli. The data analysis technique applied is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The analysis process includes the evaluation of the outer model to assess instrument validity and reliability, and the inner model to examine the relationships among latent variables, supported by t-tests and R². The findings reveal that Work-Life Balance and Workload significantly influence Work Motivation. Additionally, Workload has a direct positive effect on Job Satisfaction, while Work-Life Balance does not have a significant effect on Job Satisfaction. Moreover, Work Motivation does not significantly affect Job Satisfaction, nor does it mediate the relationship between either Work-Life Balance or Workload and Job Satisfaction.